Prevention of Online Gambling Through the Pancasila Values Approach in Forming Resilient Characters of the Young Generation - Arifin, Muh.; Putra, Zulfikar; Azis, Rahmi Ramdahani Abdul; Ramadhani, Sahra; Umpi, Ridwan (JUPE : Jurnal Pendidikan Mandala, 2025)
Digitalization is like two blades, where one side can provide benefits but can also cause harm. One of the bad effects is online gambling. Online gambling is a game that involves betting money with the expectation of profit conducted online. The purpose of this research is to prevent social problems (online gambling) by approaching Pancasila values concretely and consequently. This research method is to use descriptive qualitative research with a literature study approach to explore ideas and references in research. The results of the study are the need for synergy between schools, families and communities in instilling and internalizing the values of Pancasila in life, through education, family and a conducive social environment can create a strong young generation that is not easily affected by the negative impact of online gambling